A Survey of Various Image Enhancement Methods on Different Types of Images - Vashisth, Anshu; Sharma, Rohitt (International Journal of Computer Sciences and Engineering, 2015)
The main aim of this survey is to compare different image enhancement methods. The basic purpose of enhancement is to increase the interpretability of pixels in images so that a good quality image can produce as an output image. Removal of noise from an image using filtering is known as image enhancement. When we talk about human perception we can’t say directly that which image is good or noisy because there is no slandered measurement through which we can measure the quality of good image. Image enhancement plays important role when we use enhanced image for further processing like for number plate recognition. This paper will provide idea about already existing enhancement techniques which are frequently used in these days. This paper will provide idea that which technique is better in which case.